The -th derivative of the function at the point x = 0, where is even, is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To make things easier, we can rewrite f ( x ) as
f ( x ) = 1 − x 2 1 = k = 0 ∑ ∞ x 2 k
With radius of convergence ∣ x ∣ < 1
Since we have to evaluate the n -th derivative at x = 0 , we can use this latter formula
f ( x ) = 1 + x 2 + x 4 + x 6 + ⋯
Since n is even, there is a term of the form x n
If we derive n times, al terms from 1 up to x n − 2 wanish. We now proceed to find the n -th derivative of x n
d x d ( x n ) = n x n − 1
d x 2 d 2 ( x n ) = n ( n − 1 ) x n − 2
⋮
d x n d n ( x n ) = n ( n − 1 ) ( n − 2 ) ⋯ 2 ⋅ 1 = n !
Since all the terms from x n + 2 onwards after the procedure have at least a factor of x , when we plug in 0 they vanish too, making the answer
f ( n ) ( 0 ) = n !